1991
DOI: 10.1073/pnas.88.7.2811
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal NADPH diaphorase is a nitric oxide synthase.

Abstract: NADPH diaphorase histochemistry selectively labels a number of discrete populations of neurons throughout the nervous system. This simple and robust technique has been used in a great many experimental and neuropathological studies; however, the function of this enzyme has remained a matter of speculation. We, therefore, undertook to characterize this enzyme biochemically. With biochemical and immunochemical assays, NADPH diaphorase was purified to apparent homogeneity from rat brain by affnity chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
772
0
16

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,574 publications
(832 citation statements)
references
References 30 publications
44
772
0
16
Order By: Relevance
“…In agreement with others, we found that hyperosmotic stimulation of early and late adulthood rats triggered an activitydependent increase in NADPH-d staining density in the SON (Soinila et al, 1999;Yun et al, 2005). The increased NADPH-d staining is likely representative of neuronal NOS (nNOS) since NADPH-d has been shown to colocalize with nNOS (Dawson et al, 1991;Hope et al, 1991) but less reliably with endothelial NOS (eNOS) (Dinerman et al, 1994) and inducible NOS (iNOS) (Tracey et al, 1993). In support of this we show that stimulated NADPH-d staining is suppressed by in vitro treatment with the general NOS inhibitor, L-NNA, with highest affinity for nNOS (K i = 25 nM) and whose binding sites in the rat CNS correspond well with anti-NOS immunohistochemical staining (Kidd et al, 1995;Reif and McCreedy, 1995).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with others, we found that hyperosmotic stimulation of early and late adulthood rats triggered an activitydependent increase in NADPH-d staining density in the SON (Soinila et al, 1999;Yun et al, 2005). The increased NADPH-d staining is likely representative of neuronal NOS (nNOS) since NADPH-d has been shown to colocalize with nNOS (Dawson et al, 1991;Hope et al, 1991) but less reliably with endothelial NOS (eNOS) (Dinerman et al, 1994) and inducible NOS (iNOS) (Tracey et al, 1993). In support of this we show that stimulated NADPH-d staining is suppressed by in vitro treatment with the general NOS inhibitor, L-NNA, with highest affinity for nNOS (K i = 25 nM) and whose binding sites in the rat CNS correspond well with anti-NOS immunohistochemical staining (Kidd et al, 1995;Reif and McCreedy, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…NADPH is a required cofactor for NOS enzyme activity (Dawson et al, 1991) and NOS has NADPH-d activity (Hope et al, 1991). An enhancement of NADPH-d staining in fixed sections coincides with a respective rise in the amount of NOS protein (Kishimoto et al, 1996) and NOS gene expression (Kadowaki et al, 1994); therefore, NAPDH-d staining can be used as an indicator of NOS activity in paraformaldehyde-fixed tissue (Matsumoto et al, 1993;Young et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme survives fixation, whereas other similar enzymes are inactivated (Hope et al, 1991;Dawson et al, 1991;Hiramatsu et al, 1999). Applying this method to whole embryos, we found that NOS is present in the developing NT and adjacent tissues at 8-to 12-somite stages (see Fig.…”
Section: Results and Discussion Nitric Oxide Synthase Is Present In Dmentioning
confidence: 87%
“…The distribution of NADPH-d + neurons corroborates the findings of Brü ning and Mayer (1996) in Xenopus lae6is and is also in line with recent studies in other amphibian species Muñ oz et al, 1996) and in some reptiles (Brü ning et al, 1994;Smeets et al, 1997) (reviewed in Allaerts et al, 1997). In the rat, it was shown that NOS catalytic activity is responsible for NADPH-d staining (Hope et al, 1991;Dawson et al, 1991), although some tissues like the adrenal cortex and the liver display NADPH-d activity in the absence of NOS (Dawson et al, 1991). The faint NADPH-d reactivity in the PI of PLP-fixed Xenopus (except for the reactivity in some endothelial cells) may eventually be explained by assuming some cross-reactivity with mitochondrial cytochrome P450 reductase , as was also suggested by Smeets et al (1997) for some regions in the brain of Gekko gecko.…”
Section: Localisation Of Nos-isozymesmentioning
confidence: 99%